Identifying risks for mental health problems in HIV positive adolescents accessing HIV treatment in Johannesburg - Cluver, L; Woollett, N; Brahmbhatt, H; Bandeira, M (Routledge, 2017)
Background: Mental health problems of adolescents are underserved in low and middle-income countries where they account for a significant proportion of disease burden. Perinatally infected HIV-positive adolescents have a high prevalence of mental health disorders; however, little is known about those retained in care in South Africa. Methods: HIV-positive adolescents aged 13–19 years (n = 343) accessing five paediatric antiretroviral clinics in Johannesburg were assessed using standardized measures for depression, anxiety, post-traumatic stress disorder (PTSD), and suicidality. Descriptive and bivariate analyses were conducted on all variables using Statistica v13. Results: Twenty-seven percent were symptomatic for depression, anxiety, or PTSD; 24% reported suicidality. Peer violence was significantly correlated to all mental health problems, as was hunger, being inappropriately touched, being hit, and being female. Those reporting sickness in the past year were more symptomatic. High exposure to violence was evident. Additionally, not feeling safe at home or in the community increased risk for all mental health disorders. Knowing one’s HIV status was protective as was having dreams for the future. Conclusion: HIV-positive adolescents accessing care demonstrated high levels of mental health problems that are largely unrecognized and could potentially be addressed within health systems. Mental health difficulties are driven by social challenges that require attention.